2003
DOI: 10.1001/archinte.163.19.2323
|View full text |Cite
|
Sign up to set email alerts
|

Restless Legs Syndrome Symptoms in Primary Care

Abstract: A high prevalence of RLS symptoms was observed in this primary care population. This finding supports the need for heightened awareness in both the medical community and general population regarding this disorder, which can often be effectively treated within the primary care practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
5
15

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(115 citation statements)
references
References 12 publications
9
86
5
15
Order By: Relevance
“…The homogeneity of our study populations could account for the higher RLS prevalence we observed. This assertion is supported by a validation study of the four diagnostic RLS questions performed in a rural population of mostly white subjects in Idaho where the RLS prevalence was reported at 24%, 28 which is comparable to the prevalence of 18.3% we observed in the white population in San Diego County. Comparable to the prior reports, we found higher RLS prevalence in women and in older subjects for both HMD and NHW.…”
Section: Prevalence Of Rlssupporting
confidence: 75%
“…The homogeneity of our study populations could account for the higher RLS prevalence we observed. This assertion is supported by a validation study of the four diagnostic RLS questions performed in a rural population of mostly white subjects in Idaho where the RLS prevalence was reported at 24%, 28 which is comparable to the prevalence of 18.3% we observed in the white population in San Diego County. Comparable to the prior reports, we found higher RLS prevalence in women and in older subjects for both HMD and NHW.…”
Section: Prevalence Of Rlssupporting
confidence: 75%
“…This proportion is slightly higher than the 25% percent prevalence reported by Nichols et al, 35 and is considerably higher than the rates of 7.2% and 9% reported in 2 general population surveys. 36,37 This discrepancy may reflect that, although relatively common, RLS is often not diagnosed by physicians.…”
contrasting
confidence: 57%
“…1 Primary care patients may also be more likely to seek medical care for conditions related to RLS. 1,39 The definition of clinically significant RLS has varied across studies, from no symptom frequency or severity requirement 36 to symptoms at least twice/week with at least moderate distress. 33,40 In this study, RLS symptoms 1-2×/week were associated with significantly elevated disturbance of both sleep and mood, suggesting that RLS may be associated with substantial burden even in those with relatively low frequency of symptoms.…”
Section: Discussionmentioning
confidence: 99%